Latihan Fisik Melalui Senam Low Impact terhadap Kadar HBA1C Penderita Diabetes Mellitus - Azwaldi Azwaldi; Ismar Agustin; Imelda Erman; Fuji Rahmawati; Elvira Damayanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to see the effect of physical exercise through low-impact gymnastics on Hba1c DMT2 levels at the Makrayu Health Center in Palembang City. This research design uses Quasi-experiments with Control. The results showed that of the 33 respondents, the most were 26 people (78.8%) of gender, with the highest level of education being low education, 15 (45.4%) with a good diet program, as many as 17 (51.5%) programs good treatment as many as 23 (69.7%). Furthermore, for genetic risk factor variables, 17 (51.5%). In conclusion, there is an average difference between HbA1c levels in the second measurement for the intervention group and the control group, and the intervention group in the first and second measurements. There was a mean difference between the HbA1c levels of the intervention group in the first and second measurements. Keywords: Diabetes Mellitus Type 2, HbA1c, Low Impact Exercise